Increased Serum Angiotensin II Is a Risk Factor of Nonalcoholic Fatty Liver Disease: A Prospective Pilot Study - Yue Li; Feng Xiong; Wen Xu; Side Liu (Gastroenterology Research and Practice)
Background and Aims. Nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases. In this prospective study, we aim to explore the role of angiotensin II (Ang II) and NLRP3 inflammasome in NAFLD patients. Methods. We prospectively enrolled 96 patients in our hospital from September 2014 to February 2016. Patients were divided into two groups (NAFLD group and Control group), and the serum Ang II level, IL-1β, IL-18, and lipids were analyzed. Correlation and multivariable analyses were used in order to identify the potential risk factors of NAFLD. Results. Although the two groups share a similar demographic background, the Ang II level of NAFLD group patients was significantly higher than that of the Control group (42.18±12.37 vs. 36.69±13.90, p=0.014) when abdominal ultrasound was used for grouping. This finding was confirmed when a FibroScan Cap value was selected to divide participants into the NAFLD group and Control group (41.16±13.06 vs. 34.85±12.64, p=0.040). Multivariable analysis showed that Ang II level is an independent risk factor of NAFLD whether abdominal ultrasound (OR=1.056, p=0.037) or FibroScan Cap value (OR=1.069, p=0.013) was deemed as the diagnostic standard. Furthermore, stepwise regression analysis was carried out between Ang II with other parameters and we discovered that Ang II had a linear correlation with IL-1β. Conclusion. Ang II levels of NAFLD patients significantly increased, and elevated Ang II level is an independent risk factor of NAFLD. Our preliminary results also indicate that Ang II may promote the development of NAFLD by activating NLRP3 inflammasome.